THE INTERNALIZATION OF AKHLAQUL KARIMAH VALUES IN QURAN MEMORIZATION STUDENTS AT THE AL-RASYID ORPHANAGE TAHFIDZ AL-RASYID PONDOK ALAM BARAJO SUB-DISTRICT, JAMBI CITY - Mahyuzar Rahman (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This research explores and examines efforts to instill, internalize and implement noble moral values and character for students (santri) memorizing the Quran at Pondok Tahfid Yatim Dhuafa al-Rasyid Jambi. These values are taught and implemented in their actual daily lives. This research is qualitative, conducted in a narrative, descriptive and analytical manner, presenting the strenuous efforts of ustazd ustazah in internalizing and implementing the values of akhlaqul karimah in the daily lives of students who memorize the Qur'an at the Pondok Tahfid Yatim Dhuafa al-Rasyid Jambi. The results of this study indicate that the activities carried out by the students are all directed at implementing halal Karima behavior by the Qur'an that they read and study every time. Efforts to internalize values to implement values in the form of akhlakul karima behavior experience many challenges and difficulties from the students and the teachers (ustad, ustazah). In general, although not yet entirely successful, efforts to internalize the values of akhlaqul Karima at the conceptual level have gone well and can be seen at the level of knowledge and attitudes of the santri in real life when they are in the pesantren and when they return to their respective hometowns.